South Sudan Negotiated Independence: A Critique of African Union’s Role - Sulaiman, Abubkar o.; Agoha, Ifeanyi Chuckwu (European Journal of Sustainable Development, 2013)
The emergence of South Sudan on the 9th of July 2011 as the world's 195th independentState, 54th Member State of the African Union (AU) and 209th Federation of InternationalFootball Association member (FIFA) marks the final stage of a six year peace agreementending decades of protracted civil war. According to BBC between 1983 and the peaceagreement signed in January 2005, Sudan's civil war took nearly two million lives and leftmillions more displaced. It is reputed as Africa's longest-running civil war. The Sudanesecivil war took roots from its colonial experience, which led to forceful cohabitation ofArabic (North) and African (South) ethnic groups into a single state.